DETERMINANTES DO IMPACTO DA CONDIÇÃO DE SAÚDE BUCAL NA QUALIDADE DE VIDA DE CRIANÇAS DE 3 A 5 ANOS E SUAS FAMÍLIAS - Rocha, Juliana Schaia (2014)
The objective of this study was to analyze the determinants of the impact of oral health status on the quality of life of preschool children and their families, registered at the Family Health Strategy (FHS) in the city of Ponta Grossa/PR. The methodological design encompassed three steps: critical review of the literature, quantitative and qualitative approaches. The critical review of the literature consisted of strategic search, in order to identify the factors most frequently associated with Oral Health Related Quality of Life (OHRQoL) and to build a hierarchical model. After the articles selection, using inclusion and exclusion criteria, factors associated with preschoolers OHRQoL were listed and then grouped into a hierarchical model, which was categorized in distal, intermediate and proximal determinants. The quantitative step aimed to test the hierarchical model using a secondary database, which comprised a sample of children aged 3 to 5 years, users of the FHS. The oral health status was measured by dmtf index. The impact on OHRQoL was identified from the perception of parents by using B-ECOHIS index. Demographic, socioeconomic and behavioral characteristics of the children were also obtained. The model was tested using Poisson Regression Analysis. Variables were entered into the model according to the hierarchical level, respecting the force of the associations. The variables that showed association at a level of significance greater than 95% were maintained in the final model. The last step was a qualitative study of mothers' perception regarding their children’s OHRQoL. From the quantitative database, 26 mothers of children with severe early childhood caries were selected. Perceptions were collected through semi-structured interviews based on a script with the same dimensions of B-ECOHIS. The transcribed interviews were subjected to Thematic Content Analysis method. The hierarchical explanatory model was compiled from 13 articles that met the inclusion criteria. OHRQoL was associated with oral health status, followed by lifestyle and, finally, demographic and socioeconomic characteristics. In multivariate analysis it was demonstrated that, in distal level, the higher the age, lower income and worse living conditions, greater the impact on OHRQoL. At the intermediate level, the fact of having ever being to a dentist showed a positive association. At the proximal level, children with early childhood caries had negative impact on OHRQoL. The qualitative analysis revealed that children with severe early childhood caries had their lives affected their in function, psychological and social dimensions. Parents and families were also affected in the home routine, family relationships and the parents concerns. We conclude that there is a strong relationship between OHRQoL and demographic, socioeconomic, lifestyle and caries experience factors. According to mothers' reports, significant impacts of early childhood caries in children's lives are much more related to the experience of pain than the presence of cavities.